2017
DOI: 10.17557/tjfc.312370
|View full text |Cite
|
Sign up to set email alerts
|

Light Interception, Radiation Use Efficiency and Biomass Accumulation Response of Maize to Integrated Nutrient Management Under Drought Stress Conditions

Abstract: In order to alleviate the drought adversities on maize (Zea mays L.)biomass accumulation and radiation use efficiency (RUE), a field study was conducted under drought stress levels of D1 = well-watered, D2 = drought stress at blister stage, D3 = drought stress at blister and dough stages; and integrated nutrition levels, N0 = control, N1 = NPK, 125-60-62 kg ha-1 , N2 = NPK, 125-60-62 kg ha-1 + FYM at 10 t ha-1 , N3 = NPK, 125-60-62 kg ha-1 + FYM at 15 t ha-1 , N4 = NPK, 250-120-125 kg ha-1 , N5 = NPK, 250-120-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Greaves and Wang, (2017) concluded that long drought cycles on corn attributed to lower rainfall. Similar results emphasized the negative effect of drought on the growth of corn reported Randhawa et al (2017). Corn is sensitive to moisture stress during vegetative growth and tasselling stages (Anandhi, 2016).…”
supporting
confidence: 81%
“…Greaves and Wang, (2017) concluded that long drought cycles on corn attributed to lower rainfall. Similar results emphasized the negative effect of drought on the growth of corn reported Randhawa et al (2017). Corn is sensitive to moisture stress during vegetative growth and tasselling stages (Anandhi, 2016).…”
supporting
confidence: 81%
“…Reduced performance of these physiological parameters results due to moderate to severe water stress during cane growth and development [16]. Reduced relative water content, more negative leaf osmotic potential, and loss in turgor potential are the chief restrictions reflected in cane growth for resistance against water deficit [17][18][19]. Free proline accumulation in the leaves and roots is a response of the plant to avoid celllevel injuries due to severe drought by assisting and stabilizing the membrane, making osmotic adjustments and scavenging oxygen radicals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Drought restricts various crucial physiological processes, including growth performance, correlations between nutrients and water, photosynthesis, and assimilate partitioning, which consequently results in significant reductions in biomass production and yield ( Daryanto et al , 2017 ; Hussain et al , 2018 ). A lower absorption rate of photosynthetically active radiation, a decreased radiation use efficiency, and a decline in the harvest index are leading factors of yield reduction under limited soil moisture conditions ( Earl and Davis, 2003 ; Randhawa et al , 2017 ). Evolution has shaped the inherent potential of plant populations for morphological and physiological adjustments that mitigate the detrimental impacts of drought stress ( Farooq et al , 2009 ; Basu et al , 2016 ).…”
Section: Cereal Productivity Is Threatened By Drought Stress Worldwidmentioning
confidence: 99%